PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH MATEMATIS DI SMK INSAN KARYA NUSANTARA TAHUN PELAJARAN 2018-2019 - Yuli Yuli (Departement of Mathematics Education, 2019)
This study aims to improve student learning outcomes in the linear program material by using the Problem Based Learning method in class XI of Nusantara Workforce Vocational School in the academic year 2018-2109. This research method uses quasi experiments with quantitative forms and one group pretest-posttest research designs. Data sources were 32 students and mathematics teachers. Technique of collecting test and non-test data. Data collection tools are learning implementation plans, student and teacher observation sheets, test sheets and assessment sheets and questionnaires. The data analysis technique uses descriptive qualitative and quantitative techniques. Data analysis in general concluded that there was an increase with a difference in the value of 26. Based on the results of class XI tests before using the Problem Based Learning method in the Linear Program material the highest score was 61 while the lowest value was 30. class XI after using the Problem Based Learning method in the Linear Program system material gets the highest score is 86 while the lowest value is 67. The total value of 2533 with an average of 79. Based on the results of this study teachers are expected to improve student learning outcomes in the Linear Program material by method Problem Based Learning. The results of this study show an increase in student learning outcomes in the material of linear equations three variables using the Problem Based Learning method can improve well according to the expected goals.